BMP-2 generates a functional bone marrow niche by inducing the differentiation of local mesenchymal cells into CAR cells - Ikue Tosa; Mitsuaki Ono; Anh Tuan Dang; Ziyi Wang; Maiko Kimura; Wakana Kitagawa; Kei Ishibashi; Hang Thuy Do; Kun Zhao; Emilio Satoshi Hara; Noboru Asada; Takashi Nagasawa; et al. (Blood Advances)
Abstract: Ectopic bone marrow (eBM) holds tremendous potential as an artificial organ, serving not only in stem cell transplantation therapies but also as a controlled experimental system for analyzing cellular dynamics and interactions between cells and the matrix during the formation, maintenance, and aging of BM. Although bone morphogenetic protein-2 (BMP-2) has been reported to induce eBM formation, it remains unproven whether BMP-2–induced eBM (BMP-eBM) can provide a functional BM niche that is comparable with native BM in long bones (LB-BM). In this study, through the use of single-cell RNA sequencing and transplantation models, we demonstrate that BMP-eBM displays a microstructure, cellular composition, and functional hematopoiesis similar to LB-BM. BMP-eBM establishes an optimized microenvironment capable of supporting hematopoietic stem cells and CXC chemokine ligand 12 (CXCL12)–abundant reticular (CAR) cells, which are critical components of the BM niche. BMP-eBM was able to significantly restore survival in irradiated mice. Through parabiosis and cell transplantation experiments, we identified that in situ adipose tissue–derived CD51highCxcl12-GFP– cells are the principal source of CAR cells within BMP-eBM. Furthermore, BMP-eBM can be isolated and after preconditioning, retransplanted as an independent, functional hematopoietic organ. In conclusion, our study confirms that BMP-eBM functions effectively as a hematopoietic organ, capable of supporting and maintaining a functional BM niche. These findings underscore BMP-2 as a crucial molecule for eBM generation and suggest its potential for addressing BM-related diseases and for use as a platform for in vitro and ex vivo biomedical applications.